PENGARUH KEBUTUHAN KOORDINASI, KETIDAKPASTIAN DAN RISIKO PAJAK TERHADAP TAX AVOIDANCE (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
This study examines the effect of coordination requirements, uncertainty and risk atax on tax avoidance. The study uses data from the Indonesia Stock Exchange(IDX). The study population is the companies listed on the Stock Exchange from2008 to 2012 Based on the population obtained 31 companies that meet the criteriaspecified, so that the data obtained poled 155. These results prove the highercoordination requirements (the more complex organization of the company) the taxavoidance that is made by the company will be more aggressive. This is due to therecognition of the fiscal costs associated with the sale of any growing businesssegments minimize the amount of tax payments are borne by the company.Increasingly companies are in uncertainty, then the tax avoidance by the companyincreasingly aggressive. This is due to the company utilizing the maximum taxplanning at the time of restructuring the company to use the book value, thusminimizing income to tax. The higher the tax risks to be faced perusahaanmaka taxavoidance by the company increasingly ineffective. This is due to any operationalactivities and decisions that managers consider the element of uncertainty and risk.Activities and the operational decisions will contribute to realizing the overall risk ofacquired companies, including tax risk.Keywords: Tax avoidance, tax planning, coordination, uncertainty, risk tax